Tidal-induced and wind-driven ocean surface current data analysis derived from HF radar in Bali Strait - Aldini, I; Permanasari, AE; Hidayat, R; Ramdhani, A (IOP conference series. Earth and environmental science, 2024)
The ocean surface currents (OSC) are subject to the influences of surface wind, tidal conditions, and various other factors. Understanding these forces is essential for efficient coastal management, port activities, environmental surveillance, and the precise forecasting of ocean currents in the region. This study examined ocean surface current (OSC) data in the Bali Strait from December 2020 to November 2021. The analysis used HF radar data and the DCCA (De-trended Cross-Correlation) method. The DCCA approach examined the correlation between OSC with tidal and wind data. The study demonstrated the capabilities of HF radar data and the DCCA technique in providing valuable insights into OSC behaviours associated with tidal and wind impacts. The peak correlation value was observed when the OSC value reached its highest point in July 2021. The study showed that, overall, the correlation of OSC with tide data surpassed its correlation with wind data, emphasizing the significant influence of both tidal and wind forces on the ocean surface current in the Bali Strait. Tidal forces exhibited a stronger correlation with OSC, highlighting their crucial roles in shaping ocean surface currents in the region. These discoveries are essential for enhancing our comprehension of ocean surface currents in several sectors, especially for their application in environmental monitoring and forecasting ocean currents to maintain environmental safety and efficient coastal management practices.